Euphemisms in Élong Assimellereng Transliteration of Muh. Salim - Siti Arisa Erlin; Syamsudduha Syamsudduha; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract: This research is a qualitative descriptive study which aims to describe the forms and functions of euphemism in the élong assimellereng transliteration of Muh. Salim. Data collection techniques in this study were documentation techniques, reading techniques and note taking techniques. Data analysis techniques, namely: identification, classification, analyzing, and describing data according to the theory of Alland and Burridge. The results of this study fousd thet there are eight forms of euphemism in élong assimellereng, including figurative expression, metaphor, flipansi, remodeling, circumlocution, one word to replace another word, hyperbole, and colloquial. Meanwhile, in the euphemism function, four functions were found in élong assimellereng, namely, protection, encouragement, fraud, and advocacy.